University student: Factors that contribute to the consumption of psychoactive substances (Research, Society and Development, 2021)
The abusive consumption of alcohol, tobacco, and other substances is characterized as a worldwide public health problem. In Brazil, the consumption of these substances has media influence, and the lack of public policies, inspection and sales control, allow access to these substances and early consumption. This way, the objective was to describe the factors that contribute to the consumption of psychoactive substances among university students. This is a cross-sectional and descriptive study, carried out in a private university located in the municipality of São Luís-MA. There were 451 students enrolled in the Nursing, Medicine, Dentistry, and Psychology courses. The instruments were used for data collection: Sociodemographic Data Questionnaire; Scale for Evaluation of Disorders due to Alcohol Use (AUDIT) and Cannabis Abuse Screening Test - CAST. The SPSS software (version 21) was used to obtain descriptive statistics for the analysis of the data obtained. Of the respondents, (80.8%) were female and (19.0%) were male, with an average age between 21 and 25 years (53.7%). The most consumed SPA by these students were respectively Alcohol, Marijuana and Stimulants. The following associations were found when dealing with the associated factors: religion, institutional support, having suffered aggression, involvement in aggression after the use of alcoholic beverages, drunk driving, having been a passenger of an alcoholic driver, age who consumed alcoholic beverages, and use of stimulants.